Human papillomavirus vaccine against cervical cancer: Opportunity and challenge - Wang, Renjie; Pan, Wei; Jin, Lei; Huang, Weiming; Li, Yuehan; Wu, Di; Gao, Chun; Ma, Ding; Liao, Shujie (Cancer letters, 2020)
Cervical cancer is one of the most common cancers threatening women's health, and the persistent infection of high-risk human papillomavirus (HPV) is closely related to the pathogenesis of cervical cancer and many other cancers. The carcinogenesis is a complex process from precancerous lesion to cancer, which provides an excellent window for clinical prevention, diagnosis, and treatment. However, despite the various preventions and treatments such as HPV screening, prophylactic HPV vaccines, surgery, radiotherapy, and chemotherapy, the disease burden remains heavy worldwide. Currently, three types of prophylactic vaccines, quadrivalent HPV vaccine, bivalent HPV vaccine, and a new nonavalent HPV vaccine, are commercially available. Although these vaccines are effective in protecting against 90% of HPV infection, they provide limited benefits to eliminate pre-existing infections. Therefore, new progress has been made in the development of therapeutic vaccines. Therapeutic vaccines differ from prophylactic vaccines in that they aim to stimulate cell-mediated immunity and kill the infected cells rather than neutralizing antibodies. This review aims at systematically covering the progress, current status and future prospects of various vaccines in development for the prevention and treatment of HPV-associated lesions and cancers and laying foundations for the development of the new original vaccine. •Recent advances in HPV-related cancer biology and the viral action in carcinogenesis.•Development, current status, limitations, and prospects of prophylactic HPV vaccines.•Characteristics of several vaccine platform technologies that are being applied to the therapeutics for HPV diseases.•Research advances and further exploration of HPV vaccines.